Acute immune thrombocytopenic purpura triggered by insect bite - Namdev R; Dutta S; Singh H (Wolters Kluwer Medknow Publications, 2009)
Idiopathic Thrombocytopenic Purpura (ITP) is a blood disorder characterized by an abnormal decrease in the number of platelets in the blood. Acute thrombocytopenic purpura is most commonly seen in young children, with a sudden onset, following a viral illness, vaccination or an insect bite. The report is a rare case of ITP, which was triggered by a honey-bee bite and caused continuous intermittent bleeding from the gingival sulcular region of the maxillary left permanent first molar, and ecchymotic spots on the forehead, scalp, and lower limbs. A complete hemogram revealed severe thrombocytopenia with platelet count as low as 15,000/mm3. The patient was immediately hospitalized and administered platelet replacement and medication. With this report, the authors, as dentists, emphasize the significance of recognition, early diagnosis, and referral of such patients with bleeding disorders to specialized centers, for prompt treatment.